Three-dimensional kinematic analysis of the snatch technique for lifting different barbell weights - Hadi, G.; Akkus, H.; Harbili, E. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to investigate the effects of increased barbell loads on barbell and body kinematics of the snatch lifts at 60, 80, and 100% of 1 repetition maximum and to evaluate the biomechanics of snatch technique. The study was performed on 7 elite male weightlifters of the Turkish national team. Four cameras operating at 50 fields per second were used to record the lifts. For 3D kinematic analysis of center of gravity (CG) and barbell movement, the points on the body and the barbell were digitized by using an Ariel Performance Analysis System. There were significant differences between the vertical work values (p < 0.05). The power values of the 3 snatch lifts were also found to be significantly different (p < 0.05). Another significant difference (p < 0.05) was observed between maximum vertical displacement of the barbell, maximum vertical velocity of the barbell, maximum vertical displacement of CG, the vertical velocity of CG during the turnover under the barbell. The results demonstrated that vertical and horizontal kinematics of the barbell and body decreased at the pull phase of the snatch technique as the barbell load increased. The power output during the second pull increased although the work done did not change, whereas work and power output increased during the first pull phase depending on the increase in the barbell weight. The finding of this study suggested that weightlifters had to perform the turnover under the barbell and the catch phase faster, because when the barbell weight was increased at snatch lift, vertical kinematics of the barbell decreased.